Effects of Herbal-Acupuncture with Rosae Laevigatae Fructus Extract at KI10(Umgok) on Osteoporosis in Ovariectomized Mice - Kim Dong-soo; Kim Jeoung-ho; Kim Young-il (Korean Pharmacopuncture Institute, 2009)
Objective & Methods : The purpose of this study was to observe the effects of herbal-acupuncture with Rosae Laevigatae Fructus extact(RLF-HA) at KI10(Umgok) on osteoporosis in ovariectomized(OVX) ddy mice. We carried out several experimental items to analyze the changes in body weight, uterine weight, uterus index, tibial length, the ash bone weight, tibial BMD, serum ALP, serum osteocalcin, serum Ca, and the levels of Ca, P, Ca/P ratio in tibia, and we performed histological and histomorphological analysis as well. Results : 1. Herbal-acupuncture with Rosae Laevigatae Fructus at KI10(Umgok) and saline injection at KI10(Umgok) significantly inhibited the reduction of tibial calcium level in ovariectomized mice. 2. Herbal-acupuncture with Rosae Laevigatae Fructus at KI10(Umgok) significantly inhibited the increase of tibial osteoclast cells in ovariectomized mice. 3. Herbal-acupuncture with Rosae Laevigatae Fructus at KI10(Umgok) significantly inhibited the reduction of tibial trabecular bone thickness(TBT) in ovariectomized mice. 4. Herbal-acupuncture with Rosae Laevigatae Fructus at KI10(Umgok) significantly inhibited the overgrowth of tibial growth plate length(GPL) in ovariectomized mice. Conclusion : These results suggested that herbal-acupuncture with Rosae Laevigatae Fructus at KI10(Umgok) has a therapeutic effect on osteoporosis, and to be put to practical use in the future osteoporosis clinic.